Decision Support System on Social Stability Governance Based on Scenario Approach - L. Schultz, V; V. Kulba, V; K. Avdeeva, Z; B. Shelkov, A; V. Chernov, I (International Journal of Engineering and Technology, 2018)
In modern conditions, it is necessary to organize effective information support for governance processes ensuring social stability on the basis of a comprehensive outpacing analysis of threats to regional security and sources of vulnerability of socio-economic systems, mechanisms to reduce uncertainty in the preparation and implementation of strategic and medium-term governance decisions, and improve their effectiveness in relation to the changing situations and in the external environment. The results presented in this paper are an evolution of the methodology of scenario analysis in the direction of developing formalized methods for analyzing and synthesizing alternative scenarios for the development of the situation in the social sphere and the means of supporting them.Â Â